Imaging Recommendations for Theranostic PET-CT in Oncology - Parghane, Rahul V.; Mahajan, Abhishek; Chakrabarty, Nivedita; Basu, Sandip (Indian Journal of Medical and Paediatric Oncology, 2023)
We in this article have presented a review of the guideline recommendations on theranostic positron emission tomography-computed tomography (PET-CT) imaging which will be helpful to assist practitioners in providing appropriate patient care. Multiple guidelines by different societies and medical associations provide standards for diagnosis, imaging, and treatment of cancer patients. They have generated a number of recommendations related to 68Ga-DOTATATE and 68Ga-PSMA-11 PET-CT, which are the classical examples of theranostic PET-CT imaging in current practice.
Keywords: theranostics; PET-CT; 68Ga-DOTATATE PET-CT; 68Ga-PSMA-11 PET-CT; FAPI PET-CT; neuroendocrine tumors; prostate cancer; PRRT